Strategi Pemanfaatan Bisnis Digital dalam Memperluas Jejaring UMKM: Pengabdian kepada Masyarakat di Desa Sinartanjung-Banjar - Fani, andifa Dwi; Agung, Ahmad; Anggraeni, Selly; Safitri, Aisah Dian; Nulaila, Nurlaila; Rosidah, Rani (Khidmat, 2023)
The aim of this community service article is to find out what problems MSMEs in Sinartanjung Village are facing in relation to digital business. Sinartanjung Village has a lot of potential to use digital business, especially in the fields of agriculture, plantation and trade. This research uses descriptive research methods with a qualitative approach. Data collection techniques were observation, interview and document review. The research site is Sinartanjung village, Pataruman district, Ciamis regency. From the research findings, it is known that digital marketing makes it easier for MSMEs players to provide information and interact directly with consumers, expand market share, increase awareness and increase sales for MSMEs players.